Characterization, Local, Gunungkidul - Kristamtini, Kristamtini; AL KS, Prajitno (Jurnal Ilmu-Ilmu Pertanian, 2009)
The local Segreng red rice has been recognized in Gunung Kidul since the 1940s. Testing was done by tracing Segreng's existence, then selecting, characterizing, and introducing its description during 2005-2007. Testing was done in six villages: (1) Ngeposari, in Semanu Sub-District, (2) Pacareja, in Semanu Sub District, (3) Genjahan in Ponjong Sub-District, (4) Genjahan in Ponjong Sub-District, (5) Sumberwungu, in Tepus Sub-District, and (6) Mulo in Wonosari Sub-District. Qualitative character observation was done on location based on rice plant characterization, vegetative characteristics (height, leaf length, flag leaf width) and generative characteristics (number of cluster number of solid grain, number of hollow grain) and laboratory testing. Research resulted that segreng differed to Aek Sibundong and was a sole variety as to be listed in the genetic resource collection.